Poly(silsesquioxanes) derived from the hydrolytic condensation of organotrialkoxysilanes containing hydroxyl groups - Dell'Erba, Ignacio Esteban (2003)
Organotrialkoxysilanes containing secondary hydroxyl groups were synthesized by reacting 1 mole of (3-aminopropyl)triethoxysilane (APS) with 1 or 2 mole of phenylglycidylether (PGE). Resulting products, APS-PGE and APS-PGE2, respectively, were subjected to hydrolytic condensation at 50 °C during 24 h. For APS-PGE, the reaction was performed using a molar ratio [H2O]/Si=3, without addition of an external catalyst. For APS-PGE2, the reaction was catalyzed by HCOOH or NaOH. Resulting poly(silsesquioxanes) (PSSO) were characterized by size exclusion chromatography, Fourier-transformed infrared spectroscopy and matrix-assisted ultraviolet laser desorption/ionization time-of-flight mass spectrometry (UV-MALDI-TOF MS). PSSO derived from APS-PGE and APS-PGE2, catalyzed by HCOOH, exhibited a relatively narrow distribution of polyhedral structures. This constitutes a simple one-step synthesis of polyhedral oligomeric silsesquioxanes (POSS) functionalized with amine and/or hydroxyl groups. The directionality of the reaction pathway towards the formation of polyhedral structures was ascribed to the formation of intramolecular Si-O-C bonds through the reaction of SiOEt or SiOH groups with secondary hydroxyl groups. Intramolecular Si-O-C bonds were found in the structures of APS-PGE and APS-PGE2, and in most of the species of the PSSO obtained from the NaOH-catalyzed reaction of APS-PGE2. A small fraction of surviving Si-O-C bonds was also found in the polyhedral structures of the PSSO derived from the hydrolytic condensation of APS-PGE and APS-PGE2 catalyzed by formic acid. By usual organic reactions transforming hydroxyl groups into other functional groups, it is possible to generate narrow distribution of multi-functionalized POSS starting from an OH-functionalized organotrialkoxysilane.